Impact of different vegetable fats and oils on instrumentally measured color and texture of processed chicken sausages - Pejkovski Zlatko; Silovksa NIkolova Aleksandra; Belichovska Katerina; Gasperlin Lea; Polak Tomas; Zlender Bozidar; Lilic Slobodan; Ockerman Herber (Tehnologija mesa, 2009)
The effect of vegetable fats and oils on instrumentally measured color and texture of processed chicken sausages was investigated using six variants of sausages: control, containing pork back fat (Po); olive oil (O); rapeseed oil (R); sunfower oil (S); palm fat (Pa) and a mixture (Mi) of 60 % rapeseed oil (R) and 40 % palm fat (Pa). Palm (Pa) fat resulted in the darkest (p 0,05) surface color of processed poultry sausages. High intensity red color was most desirable on the sausage surface and was obtained with palm (Pa) fat and a mixture (Mi) of 60% palm fat and 40% rapeseed oil (R). Incorporation of all other plant oils and fats increased yellowness on the surface of processed poultry frankfurters. Palm (Pa) and pork (Po) fat, that are rich in saturated fatty acids, (p 0.05) darkened color on poultry sausages at the fresh cross sectional plane. Pork (Po) fat also (p 0.05) improved the red color hue at the fresh cross section plane of sausages. Plant oils, when not used in a mixture with palm fat (p 0.05) increased the Warner Bratzler Shear Force (WBSF) making the product harder and rmer in texture.
Keywords: processed chicken, frankfurter-sausages, plant fats, plant oils, color, texture